Experimental and numerical investigation of the behaviour of CFRP strengthened CHS beams subjected to bending. (15th April 2016) - Kabir, M.H.; Fawzia, S.; Chan, T.H.T.; Gamage, J.C.P.H.; Bai, J.B.
Highlights: Two different failure modes were observed depending on CFRP layer orientation. The effect of layer orientation on failure load was not significant. CFRP with higher modulus increases strength and stiffness of beam significantly. The LHL and LLH layer combinations of CFRP show very similar structural behaviour. Abstract: This paper presents the results of an experimental and numerical program to investigate the circular hollow section (CHS) beams, strengthened using Carbon Fibre Reinforced Polymer (CFRP) sheets. The circular hollow shaped steel beams bonded with different CFRP layer orientations were tested under four-point bending. The mid-span deflection, service load and failure load were recorded. The LHL (where L, first inner longitudinal layer, H, second hoop layer and L, third outer longitudinal layer) and LLH (where L, first inner longitudinal layer, L, second longitudinal layer and H, third outer hoop layer) layer oriented strengthened beams perform slightly better than HHL (where H, first inner hoop layer, H, second hoop layer and L, third outer longitudinal layer) layer oriented strengthened beams. The LHL and LLH layer oriented treated beams showed very similar structural behaviour. Numerical analyses were then conducted on the CFRP strengthened steel CHS beams. The validity of the models has been assessed by comparing the failure loads and mid-span deflections. The effects of various parameters such as bond length, section types, tensile modulus of CFRP, adhesive layer thickness and adhesive types have been studied.